2003
DOI: 10.1046/j.1365-2249.2003.02019.x
|View full text |Cite
|
Sign up to set email alerts
|

T cell vaccination in multiple sclerosis patients with autologous CSF-derived activated T cells: results from a pilot study

Abstract: SUMMARYMyelin-reactive T cells are considered to play an essential role in the pathogenesis of multiple sclerosis (MS), an autoimmune disease of the central nervous system. We have previously studied the effects of T cell vaccination (TCV), a procedure by which MS patients are immunized with attenuated autologous myelin basic protein (MBP)-reactive T cell clones. Because several myelin antigens are described as potential autoantigens for MS, T cell vaccines incorporating a broad panel of antimyelin reactivitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 59 publications
0
28
1
5
Order By: Relevance
“…Third, the anti-IL-17 antibody treatment of sub-STZ-treated animals that received the adoptive transfer of 10 × 10 6 Th17-polarized cells decreased the blood glucose level, showing that the suppression of IL-17 protects against the progression of autoimmune diabetes induced by STZ. Previous study showed that TCV exerts immunomodulatory effect through the induction of both anti-idiotypic response, which was specific to the immunizing cells and anti-ergotypic T cells more toward activated T cells in other autoimmune diseases [46][47][48][49]. It is not unlikely that suppression of Th17 cells is the result of TCV-induced anti-ergotypic effect because Th17 cells are an activated T-cell subset.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the anti-IL-17 antibody treatment of sub-STZ-treated animals that received the adoptive transfer of 10 × 10 6 Th17-polarized cells decreased the blood glucose level, showing that the suppression of IL-17 protects against the progression of autoimmune diabetes induced by STZ. Previous study showed that TCV exerts immunomodulatory effect through the induction of both anti-idiotypic response, which was specific to the immunizing cells and anti-ergotypic T cells more toward activated T cells in other autoimmune diseases [46][47][48][49]. It is not unlikely that suppression of Th17 cells is the result of TCV-induced anti-ergotypic effect because Th17 cells are an activated T-cell subset.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of this CD8 ϩ antiidiotypic T cell regulation is relatively well characterized and is found to involve components of target T cell receptor in the context of MHC class I molecules (3)(4)(5)(6). However, it remains to be determined whether depletion of circulating autoreactive T cells alone would be sufficient to induce or account for clinical improvements seen in some of MS patients treated with T cell vaccination (3,5,15,(20)(21)(22)(23). In this regard, it is insightful that Cohen and colleagues (7,12) and other investigators showed in experimental autoimmune encephalomyelitis experiments that only activated, but not resting, encephalitogenic T cells could induce full protection through T cell vaccination.…”
Section: Reactivity Patterns and The Recognition Of Il-2 Receptor-dermentioning
confidence: 99%
“…Similarly, the results of a pilot vaccination trial with cerebrospinal fluidderived activated T cells seem promising but need to be confirmed in a larger trial (123).…”
Section: Ga (Copolymer 1 Copaxone)mentioning
confidence: 99%